Organisation of Healthcare Systems in the Context of the Healthcare Models Implemented - Katarzyna ŁASIŃSKA; Ryszard STRYJSKI; Waldemar WOŹNIAK; Sławomir ZWIERZCHLEWSKI (Communications of International Proceedings, 2020)
This article presents the health systems of selected European countries. Different models of health systems and their implementation are presented. The solutions used in different European countries provide an opportunity for comparison and proposals that can improve the efficiency of the health systems.
Keywords: Health Policy; Public Health; Health Protection; Health System.